DAMPAK PANDEMI TERHADAP KETAHANAN KELUARGA PEDAGANG KAKI LIMA DI KOTA PROBOLINGGO - Rifki Nur Hidayat; Imanuddin Abil Fida (LPPM STAI Muhammadiyah Probolinggo, 2023)
Since the end of 2019, the world has been shocked by the outbreak of the corona virus or what we usually refer to as Covid-19 which has spread in almost all parts of the world. The spread of this epidemic has had a major impact on various sectors in the world order, from the cancelation of large-scale events (international sports matches) to the almost complete cancellation, the economic decline in several countries, including Indonesia. The spread of the Covid-19 virus in Indonesia greatly affected all sectors, especially in the economic sector. The impact of this economic downturn was also felt by street vendors in Probolinggo City, who experienced a decrease in income due to the PSBB policy. The impact of the decrease in the income of street vendors in Probolinggo City is very influential on the harmony of their families, it is not uncommon for differences of opinion to occur which result in arguments between husbands and wives. Especially with financial problems when the wife asks for shopping money to meet her daily needs, but the husband, during the pandemic, his income from sales has decreased drastically, even to the point where he is forced not to sell because the place they usually use to sell is closed.